KESIAPAN SUMBER DAYA MANUSIA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PALEMBANG DALAM MENGHADAPI TRANSFORMASI DIGITAL - Desti Eka Saputri; Dina Mellita (Universitas Bina Taruna Gorontalo, 2024)
This research aims to test the readiness of human resources in facing digital transformation. The method used is quantitative, the object of research is employees of the Palembang City Library and Archives Service. The respondents in this research were 94 employees of the Palembang City Library and Archives Service, collecting data using a questionnaire. Sampling in this study used a saturated sampling technique, namely sampling carried out as a whole from the total population. The analysis technique used in this research is logistic regression, which is a type of regression analysis used to describe the relationship between independent variables and dependent variables, with the dependent variable (Y) being assumed to be binary qualitative/having two categories. The data analysis technique was carried out using SPSS version 20. Based on the results of the binary logistic regression analysis, it was found that significant factors in the readiness of human resources in facing digital transformation were age, length of work, personality and skills. Meanwhile, factors that were not found to be significant in the readiness of human resources in facing digital transformation were innovation & optimism. It is hoped that this research can add information and reading references, thereby increasing knowledge about the digital transformation process.